2011
DOI: 10.1007/s10518-011-9335-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between topographic irregularities and seismic ground motion investigated using a hybrid FD-FE method

Abstract: A hybrid method combining finite element and 4 th -order finite difference techniques is developed to model SH and P-SV seismic wave propagation in a 2D elastic medium with irregular surface topography. Both the classic staggered grid finite difference scheme and the partially staggered grid scheme are tested. The accuracy of the hybrid method is studied by comparison with a semi-analytical and another numerical method. Subsequently, to study the amplification, numerical simulations of seismic wave propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Combining different methods such as FDM and FEM has also been proposed (e.g. Moczo & Kristek 2005;De Martin et al 2007;Ducellier & Aochi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Combining different methods such as FDM and FEM has also been proposed (e.g. Moczo & Kristek 2005;De Martin et al 2007;Ducellier & Aochi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical analysis method mainly refers to the wave function expansion method [15,16]. Numerical methods include finite difference method [17], spectral element method [9], finite element method [18], boundary element method [19], and hybrid method [20]. Using the theoretical analysis method (wave function expansion method), Gao [21] reported that the peak acceleration recorded at SC1 was more than 2.5 times that at the SC4 of the Feitsui canyon (V-shape).…”
Section: Introductionmentioning
confidence: 99%
“…The feature of the earth's boundary that first comes to mind is the above-ground structure (AGS), often termed topography [56,21,19,14,4,16,20,24,25,27,32,34,42,43,47,48,57,64,65,73,75,79,111,118,119,135,171,181,183,195,216,265,279,282,283,305,322,325,344,371,383,227,228,229,327,285,270,215,85,106,225...…”
Section: Introductionmentioning
confidence: 99%
“…The AGS's affected by seismic waves can be divided into two classes: i) a 'natural' AGS such as a hill [14,25,46,55,71,73,118,131,159,181,191,193,194,197,205,241,251,256,264,268,255,278,307,376,378,85,87,153,46,212,269,106,375,326,376,325,333,264], volcano [296,282,307,219,60,219,296], mountain [177,178,351,352,353,…”
Section: Introductionmentioning
confidence: 99%